Infrared thermal imaging as a nonradiation method for detecting thermal expression characteristics in normal female breasts in China - Zeng, Jingni; Lin, Lin; Deng, Fangge (Infrared physics & technology, 2020)
•The temperature of the upper left quadrant was higher than that of the right side.•The temperature of the upper quadrant was usually higher than that of the lower quadrant.•There were no significant correlations according to age, BMI, mammary gland types and breast surface mean temperature. Infrared thermal imaging technology (IRTI) is a physical technology applied in many fields, including the screening of breast cancer. However, IRTI is still in a primary stage in our country. The purpose of this paper was to explore the characteristics of breast temperature distribution and the correlations among BMI, mammary gland types and surface temperature distributions in normal Chinese female patients. Thirty-five subjects who underwent successive IRTI and mammography (excluding those with positive findings on clinical examination or mammography) were analyzed by two experience radiologists. The breast temperature distribution of normal females was symmetrical, and the mean temperature of both sides was almost equal (left:33.13 ± 2.48 °C, right: 33.04 ± 2.55 °C, P = 0.077, n = 35). The nipple areas had the lowest temperatures among all areas of the breast; in contrast, the bilateral axillary and inframammary folds showed relatively high temperatures. The temperature of the upper left quadrant was higher than that of the right side (left:33.45 ± 2.68 °C, right: 33.30 ± 2.67 °C, P = 0.011, n = 35). The temperature in the upper quadrant was higher than that of the lower quadrant. There were no significant differences among patients with different ages, BMI and mammary gland types in surface temperature distributions. Certain expression characteristics of breast thermograms of normal females could help us determine the characteristics of abnormal women.